Identification of malic and soluble oxaloacetate decarboxylase enzymes in Enterococcus faecalis - Espariz, Martin (2011)
Two paralogous genes, maeE and citM, that encode putative malic enzyme family members were identified in the Enterococcus faecalis genome. MaeE (41 kDa) and CitM (42 kDa) share a high degree of homology between them (47% identities and 68% conservative substitutions). However, the genetic context of each gene suggested that maeE is associated with malate utilization whereas citM is linked to the citrate fermentation pathway. In the present work, we focus on the biochemical characterization and physiological contribution of these enzymes in E. faecalis. With this aim, the recombinant versions of the two proteins were expressed in Escherichia coli, affinity purified and finally their kinetic parameters were determined. This approach allowed us to establish that MaeE is a malate oxidative decarboxylating enzyme and CitM is a soluble oxaloacetate decarboxylase. Moreover, our genetic studies in E. faecalis showed that the citrate fermentation phenotype is not affected by citM deletion. On the other hand, maeE gene disruption resulted in a malate fermentation deficient strain indicating that MaeE is responsible for malate metabolism in E. faecalis. Lastly, it was demonstrated that malate fermentation in E. faecalis is associated with cytoplasmic and extracellular alkalinization which clearly contributes to pH homeostasis in neutral or mild acidic conditions. In the present study, we performed a biochemical characterization of two members of the malic enzyme family from Enterococcus faecalis. It was stated that MaeE is a malate oxidative decarboxylating enzyme whereas CitM is a soluble oxaloacetate decarboxylase. Our genetic studies showed that the citrate fermentation phenotype is not affected by citM deletion. Conversely, maeE gene disruption resulted in a malate deficient strain.